Healthcare provider and patient perspectives on access to and management of atrial fbrillation in the Northern Province, Sri Lanka: a rapid evaluation of barriers and facilitators to care - Vethanayagam, A.S.; Shivany, S.; Gooden, T.E.; Guruparan, M.; Kumarendran, B.; Gregory, Y.H.L.; Semira, M.H.; Krishnarajah, N.; Shribavan, K.; Subaschandren, K.; Hanifa, R.; Surenthirakumaran, R.; et al. (Sheron et al. BMC Health Services Research, 2022)
Atrial fbrillation (AF) is the most common cardiac arrhythmia that afects 60 million people worldwide. Limited evidence on AF management exists from low- and middle-income countries and none from Sri Lanka. We aimed to investigate the existing AF care pathway and patients’ perception on AF management to identify barriers and enablers for optimal AF care in Northern Province, Sri Lanka.
Keywords: Atrial fbrillation; Care pathways; Chronic disease management; Barriers to care; Decision making; Health seeking behaviours; Qualitative methods; Rapid evaluation